AN EPIDEMIOLOGICAL SURVEY OF THERMAL BURNS IN ADULT FEMALES IN A BURNS UNIT OF MUMBAI - Bhaskara, K G; Rana, R E; Puri, V (Indian Journal of Plastic Surgery, 2000)
This is a prospective study of 238 adult females of thermal burns admitted in the burns ward of KEM Hospital, Mumbai over a period of 16 months (from August 1997 to November 1998). Mean age was 25 years with a range of 12 to 70 years. Paediatric burns (below the age of of 12 years) were not included in the study. Flame burns accounted for 94.5% and scalds 5.4%. Majority were accidental (77.7%) followed by suicidal (21%) and homicidal (1.3%) burns. Over all mortality was 61.76%. TBSA of burns was the main factor influencing the survival.
Keywords: Burns; Epidemiology